Beclin‐1‐mediated activation of autophagy improves proximal and distal urea cycle disorders - Leandro R Soria; Sonam Gurung; Giulia De Sabbata; Dany P Perocheau; Angela De Angelis; Gemma Bruno; Elena Polishchuk; Debora Paris; Paola Cuomo; Andrea Motta; Michael Orford; Youssef Khalil; et al. (EMBO Molecular Medicine)
Abstract Urea cycle disorders (UCD) are inherited defects in clearance of waste nitrogen with high morbidity and mortality. Novel and more effective therapies for UCD are needed. Studies in mice with constitutive activation of autophagy unravelled Beclin‐1 as druggable candidate for therapy of hyperammonemia. Next, we investigated efficacy of cell‐penetrating autophagy‐inducing Tat‐Beclin‐1 (TB‐1) peptide for therapy of the two most common UCD, namely ornithine transcarbamylase (OTC) and argininosuccinate lyase (ASL) deficiencies. TB‐1 reduced urinary orotic acid and improved survival under protein‐rich diet in spf‐ash mice, a model of OTC deficiency (proximal UCD). In AslNeo/Neo mice, a model of ASL deficiency (distal UCD), TB‐1 increased ureagenesis, reduced argininosuccinate, and improved survival. Moreover, it alleviated hepatocellular injury and decreased both cytoplasmic and nuclear glycogen accumulation in AslNeo/Neo mice. In conclusion, Beclin‐1‐dependent activation of autophagy improved biochemical and clinical phenotypes of proximal and distal defects of the urea cycle.